Hamstring and lower back muscles flexibility as predictor of saddle pressures in young off-road cyclists - Vicari, Domenico Savio Salvatore; Patti, Antonino; Giustino, Valerio; Belmonte, Giacomo; Alamia, Giuseppe; Gervasi, Marco; Fernández Peña, Eneko; Palma, Antonio; Schena, Federico; Bianco, Antonino; Thomas, Ewan (Frontiers in Sports and Active Living, 2024)
Introduction While pedaling, cyclists rest their pelvis on the saddle, generating pressures on it. The pressures generated on the saddle are influenced by several factors. This study aimed to evaluate whether the flexibility of hamstring and lower back muscles could be considered a predictor of pressures in the anterior region (PAR) on the saddle. Methods For this study, 15 young off-road Italian cyclists (11m, 4f) aged 13–16 (Italian Federation categories: ES1, ES2, AL1, AL2) were recruited. Each participant was administered the V sit-and-reach (VSR) to measure the hamstring and lower back muscles flexibility. Subsequently, after performing a bike fitting, the saddle pressures during pedaling at three different intensities (100, 140, 180 W), with participants on their own bike installed on specific bike roller, were recorded. The parameters considered for statistical analysis were front pressure (%) and back pressure (%). Results The hamstring and lower back muscles flexibility, as result of the VSR test, was a predictor of saddle PAR at 100 W (R2 = 0.362, p = 0.018), at 140 W (R2 = 0.291, p = 0.038), and at 180 W (R2 = 0.349, p = 0.020) of pedaling intensity. Conclusion Higher values of the VSR could predict lower values of the pressures exerted in the front region of the saddle. The hamstring and lower back muscles flexibility may be considered a predictor of PAR on the saddle.